Self Identity Pelari Kalcer Gen Z melalui Aplikasi Strava - Soraya, Iin; Herman, Herman; Retno, Laurensia (Jurnal Cyber PR, 2025)
The development of this media also supports runners to easily record running performance. One of the media that supports runners is the Strava application, this application is dedicated to morning running can function as a way to provide training and schedule guidance, but the use of the Strava application has shifted the meaning of running activities from just a health sport to a lifestyle, self-image and self-existence, this gave rise to a phenomenon in Indonesia called Kalcer Runners. For Kalcer runners, Strava becomes a digital space to affirm who they are, not only as individuals who run, but as part of a community with a certain lifestyle so as to form a self-identity among Gen Z. This study aims to analyze the self-identity of Kalcer runners among Gen Z using the Strava application. This study uses a qualitative approach, through digital observation and in-depth interviews with Gen Z runners who actively use Strava. The results show that Strava not only functions as a tool for monitoring sports activities, but also as a symbolic space to build self-image, gain social recognition, and form a community based on a healthy and aesthetic lifestyle. The identity of Kalcer runners.